Improving Learning Outcomes Students in Science Learning through Flash Cards Student Class 4 UPT SDN Kutorejo 3 - Dewi, Titis Auliana; Wulandari, Tabitha Sri Hartati (EDUCATION JOURNAL OF INDONESIA, 2025)
Instructional Media own role important in learning , one of them For interesting attention students . Learning media Still seldom used in the environment school so that student not enough own motivation and interest Study so that impact on the results Study students . Teachers should using innovative learning media​ so that can increase results Study students . One of the interesting media in learning is a flash card media. Research This aiming For know improvement results Study student in science learning through flash card media. Research This is Classroom Action Research (CAR). Subject in study This is student class IV UPT SDN Kutorejo 3 consisting of 30 students . Data collection techniques in the study This is analysis descriptive quantitative with count results test evaluation participant educate on every its cycle , and not forget documentation during the activity process in progress as evidence ... The research results obtained is results Study students who were originally 43% in pre- cycle , increase became (63%) in cycle I and in cycle III became (83%). With Thus , the increase results Study student via flash card media increase results Study students in science learning at UPT SDN Kutorejo 3 Tuban